2018
DOI: 10.1002/jcb.27066
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of single‐cell RNA sequencing data from 3 and 7 days old mouse spermatogonial stem cells to identify their differentially expressed genes and transcriptional regulators

Abstract: Spermatogonial stem cells (SSCs), which are at the basis of spermatogenesis process, are valuable cells with different applications in biotechnology and regenerative medicine. Understanding the molecular basis of SSC self-renewal and differentiation at various developmental stages of the male organism is crucial to find key factors in the SSCs fate and function. Therefore, this study was aimed to use single-cell RNA-sequencing dataset analysis for identification of differentially expressed genes (DEGs) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…3). Sisakhtnezhad et al indicated that FkBP6 was associated with the self-renewal and maintenance of spermatogonial stem cells (SSCs), which played a key role in the process of spermatogenesis [50]. Therefore, graphene + TPP could induce reproductive toxicity by affecting the expression of FKBP6.…”
Section: Construction Of Regulatory Molecular Pathways Of Graphene + Tpp and M Galloprovincialis Interactionmentioning
confidence: 99%
“…3). Sisakhtnezhad et al indicated that FkBP6 was associated with the self-renewal and maintenance of spermatogonial stem cells (SSCs), which played a key role in the process of spermatogenesis [50]. Therefore, graphene + TPP could induce reproductive toxicity by affecting the expression of FKBP6.…”
Section: Construction Of Regulatory Molecular Pathways Of Graphene + Tpp and M Galloprovincialis Interactionmentioning
confidence: 99%
“…With the development of bulk RNA sequencing and single cell RNA-sequencing (scRNA-Seq) technology, it is possible to explore gene expression profile of different organs and different cells in one organ (10)(11)(12). The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases show the significant upregulation of Six1 in 13 cancer samples when compared with testicular germ cell tumor (TGCT) (13).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, mSSCs derived from mice aged 3 or 7 years old were analyzed to identify differentially expressed genes using the scRNA-Seq database. This analysis helped to identify core factors that are involved in germ cell development (10,11).…”
Section: Introductionmentioning
confidence: 99%